2019
DOI: 10.1002/jrs.5790
|View full text |Cite
|
Sign up to set email alerts
|

Application of Raman spectroscopy in comparative study of antiobesity influence of oxytocin and freeze‐dried extracts of Uvariodendron anisatum Verdeck (Annonaceae) in Sprague Dawley rats

Abstract: Obesity is a condition affecting a substantial number of people in the world. Obese people have increased risks of developing chronic metabolic diseases such as type II diabetes, hypertension, and cancer, among others. Predicting potential development together with rapid diagnosis of the condition followed by early interventions is therefore necessary. This work investigated, first, utility of Raman spectroscopy in performing comparative antiobesity influence studies of oxytocin and a freeze‐dried extract of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…The ability of an IR probe to quantitatively report on the local electric field is crucial for successful application to study the local structure in proteins, and numerous IR spectroscopic studies have been reported for the OT molecule. Thus, for the sake of direct comparison, the IR spectra of the OT molecule are studied experimentally and theoretically (Figure ). The theoretical anharmonic IR peak of the disulfide bond lies on 552 cm –1 , which is slightly larger than our experimental value of 547 cm –1 and other experimental values of 542 cm –1 , and the strength of the IR peak of the disulfide bond is much smaller than that of amide-I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of an IR probe to quantitatively report on the local electric field is crucial for successful application to study the local structure in proteins, and numerous IR spectroscopic studies have been reported for the OT molecule. Thus, for the sake of direct comparison, the IR spectra of the OT molecule are studied experimentally and theoretically (Figure ). The theoretical anharmonic IR peak of the disulfide bond lies on 552 cm –1 , which is slightly larger than our experimental value of 547 cm –1 and other experimental values of 542 cm –1 , and the strength of the IR peak of the disulfide bond is much smaller than that of amide-I.…”
Section: Resultsmentioning
confidence: 99%
“…De Barros et al investigated the Fourier transform infrared information of OT and sustained release using natural rubber latex membranes and identified absorption IR peaks for functional groups of OT . Birech et al studied the antiobesity influence of OT using Raman spectroscopy and confirmed that OT played an important role in obese rats . Joly et al studied optical and structural properties of copper–oxytocin dictations in the gas phase, and the experimental and theoretical results showed a global enhancement of the photofragmentation yield as compared to the one recorded for the doubly protonated OT .…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocin receptor CD, [30] NMR, [31] FTIR, [32] Raman [33] Cyclosporin 1202.61 (11 aa) aL*L*V* (Bmt) * (Abu)G*LVLA (Cyclization at D-Ala1-Ala11) Cyclic peptide calcineurin inhibitor CD, [34] X-ray, [35] PXRD, [34] NMR, [36] FT-IR [37] Leuprolide 1209.42 (9 aa) Pyr-HWSYlLRP-NHEt (Pyr = L-pyroglutamyl).…”
Section: Cyclic Peptidementioning
confidence: 99%